Beyond the clot: perfusion imaging of the pulmonary vasculature after COVID-19. Issue 1 (January 2021) - Dhawan, Ranju T; Gopalan, Deepa; Howard, Luke; Vicente, Angelito; Park, Mirae; Manalan, Kavina; Wallner, Ingrid; Marsden, Peter; Dave, Surendra; Branley, Howard; Russell, Georgina; Dharmarajah, Nishanth; et al.
Summary: A compelling body of evidence points to pulmonary thrombosis and thromboembolism as a key feature of COVID-19. As the pandemic spread across the globe over the past few months, a timely call to arms was issued by a team of clinicians to consider the prospect of long-lasting pulmonary fibrotic damage and plan for structured follow-up. However, the component of post-thrombotic sequelae has been less widely considered. Although the long-term outcomes of COVID-19 are not known, should pulmonary vascular sequelae prove to be clinically significant, these have the potential to become a public health problem. In this Personal View, we propose a proactive follow-up strategy to evaluate residual clot burden, small vessel injury, and potential haemodynamic sequelae. A nuanced and physiological approach to follow-up imaging that looks beyond the clot, at the state of perfusion of lung tissue, is proposed as a key triage tool, with the potential to inform therapeutic strategies.